The Impact of The Turtle Beach Tourism Destination Management Model on Improving The Economy of The Ekas Buana Village Community, Jerowaru Sub-District, East Lombok District - Rudi Azhari; Prayitno Basuki; Adhitya Bagus Singandaru (Westscience Press, 2024)
This study aims to determine the management model of turtle beach tourist destinations, and to determine the impact of the turtle beach tourist destination management model on improving the economy of the Ekas Buana Village community, Jerowaru District, East Lombok Regency. This research is qualitative research, data collection techniques using unstructured observation techniques, in-depth interviews, and documentation. Determination of informants using purposive sampling. Data analysis techniques used are data collection, data reduction, data presentation, and conclusion drawing/verification. The results of the research based on the data as well as the results of interviews and field findings show that the turtle beach destination uses the management of the Community-Based tourism (CBT) model, an approach that focuses on active participation and empowerment of local communities in the management and development of tourism destinations which are managed by the Pokdarwis and the community around the turtle beach tourist destination. This shows that the impact of the management of the Community-Based Tourism (CBT) model on the economy of the Ekas Buana Village community has a positive impact on economic activities consisting of increasing income and opening up jobs and business opportunities for the community as tourism actors. The community around the tourist attraction gets a good livelihood as a food and beverage trader, and as a restaurant employee as well as a surfboard rental provider for tourists who want to surf on the turtle beach.